Development of poly-2-ethyl-2-oxazoline coated gold-core silica shell nanorods for cancer chemo-photothermal therapy - Moreira, André Ferreira (2018)
Aim: Develop a new poly-2-ethyl-2-oxazoline (PEOZ)-based coating for doxorubicin-loaded gold-core mesoporous silica shell (AuMSS) nanorods application in cancer chemo-photothermal therapy. Methods: PEOZ functionalized AuMSS nanorods were obtained through the chemical grafting on AuMSS of a PEOZ silane derivative. Results: The PEOZ chemical grafting on the surface of AuMSS nanorods allowed the neutralization of nanodevices’ surface charge, from -30 to -15 mV, which improved nanoparticles’ biocompatibility, namely by decreasing the blood hemolysis to negligible levels. In vitro antitumoral studies revealed that the combined treatment mediated by the PEOZ-coated AuMSS nanorods result in a synergistic effect, allowing the complete eradication of cervical cancer cells. Conclusion: The application of the PEOZ coating improves the AuMSS nanorods performance as a multifunctional combinatorial therapy for cervical cancer.